PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL PADA ELEMEN TEKNIK LIPATAN NAPKIN FASE F DI SMK 2 MAGETAN - Anis Salsabila; Febriani Lukitasari; Luthfiyah Nurlaela; Diwyacitta Antya Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research project in the R&D (Research & Development) department aimed to develop a video tutorial on napkin folding technique F at SMKN 2 Magetan, evaluate the suitability of the materials and media, and assess student feedback. The development of this media was prompted by the challenge students face in remembering the folding steps when practising independently. Therefore, the development of structured video tutorials was necessary to provide visualisation that could be studied repeatedly by students. The 4D model was applied, which only covers three stages (Define, Design, Development). The media were created using Adobe Premiere Pro and CapCut, resulting in three video tutorial sections for use in teaching. This is supported by the results of expert evaluations of the material (92% very suitable), the media (85.56% very suitable) and student responses with an average percentage of 90.10% (very suitable). These results show that the learning media created is highly effective in engaging students in the process of understanding the material on napkin folding techniques.